*MWELex – MWE Lexica of Croatian, Slovene and Serbian Extracted from Parsed Corpora (Informatica, 2015)
The paper presents *MWELex, a multilingual lexical repository of Croatian, Slovene and Serbian multiwordexpressions that were extracted from parsed corpora. The lexica were built with the custom-builtDepMWEx tool which uses dependency syntactic patterns to identify MWE candidates in parse trees. Theextracted MWE candidates are subsequently scored by co-occurrence and organized by headwords producinga resource of 23 to 48 thousand headwords and 3.2 to 12 million MWE candidates per language. Theevaluation of the lexicon, performed on Croatian and Slovene, shows an overall precision of just over 50%for Croatian but as high as 85% for Slovene. Similarly, precision over specific syntactic patterns variesgreatly, 0.167-0.859 for Croatian, 0.158-1.00 for Slovene. The possible extension of the tool is demonstratedon a simplistic distributional-based extraction of non-transparent MWEs and cross-lingual linkingof the extracted lexicons.